Gambaran Kepercayaan Diri Korban Bullying pada Remaja di KEC Bua - Fitria, Aviyatul; Kadir, Abdul; Marhani, Marhani (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
This study aims to describe the self-confidence of adolescents who are victims of bullying in Bua District. Using a qualitative method with a phenomenological approach, data were collected from four main informants aged 12–24 years and four supporting informants through purposive sampling. Primary data were obtained from in-depth semi-structured interviews, observation, recordings, and documentation, while secondary data came from literature, journals, and related documents. The results show that bullying, especially verbal and social forms such as exclusion, humiliation, and gossip, causes a decline in self-confidence, social interaction difficulties, and social withdrawal among adolescents. Victims tend to experience trauma, fear, shame, and prolonged anxiety, which negatively affect their social relations and emotional balance. However, the findings also highlight that supportive social environments, including family, peers, and inner circles, are essential for victims’ psychological recovery and rebuilding their self-confidence. Creating safe, positive, and accepting environments can become a crucial foundation for restoring adolescents’ self-esteem and fostering their personal growth after experiencing bullying.